Using blockchain and digital marketing to build trust in green projects - Ali Al-Ababneh Hassan; Ahmad Alkhudierat Noor; Mohd Salim Barhoush Fawaz; Habes Almajali Ahmad; Ibragimkhalilova Tatyana; Ibrahim Mugableh Mohamed (E3S Web of Conferences)
The article is devoted to the study of the application of blockchain technologies and digital marketing to increase trust in green projects focused on sustainable development and environmentally friendly technologies. In the context of modern information overload and a high degree of consumer mistrust of environmental initiatives, it is important to use innovative tools that will ensure transparency, security and reliability of information. Blockchain as a distribution database allows us to guarantee the immutability of data on the origin of products and production processes, which is especially important in the field of green technologies, where there is often a risk of “greenwashing” - falsification of environmental characteristics of products. In turn, digital marketing using tools such as social networks, SEO and content marketing helps to effectively convey information about green initiatives to the target audience and create trust. The article analyzes existing methods and successful examples of blockchain implementation in the marketing strategies of companies operating in the field of renewable energy and sustainable production. The prospects and challenges of implementing these technologies, as well as their synergy for creating transparent and trusting relationships between companies and consumers are also considered.